Automated Intravenous Drug Administration and Dosage Verification System for ICU Patients (International Journal of Nursing Ethics, and Health Care Management, 2026)
Automated Intravenous (IV) drug administration systems are revolutionizing patient care in Intensive Care Units (ICUs) by improving accuracy, safety, and efficiency in medication delivery. Critically ill patients often require continuous infusion of life-saving drugs, where even minor dosage errors can lead to serious complications or adverse outcomes. Traditional manual infusion methods are highly dependent on human intervention, increasing the risk of errors such as incorrect dosage, improper infusion rates, and delayed response to physiological changes. Automated systems address these challenges by integrating smart infusion pumps, advanced sensors, Artificial Intelligence (AI), and closed-loop control mechanisms. These technologies enable real-time monitoring of patient parameters and automatic adjustment of drug delivery based on clinical conditions. Additionally, dosage verification techniques such as drug libraries, barcode scanning, and algorithm-based validation enhance the accuracy of medication administration. The integration of these systems with electronic health records further ensures consistency between prescribed and delivered treatments.
Keywords: Artificial Intelligence; Automated IV System; Closed-Loop Control; Dosage Verification; ICU; Patient Safety; Smart Infusion Pump; Medication Error Reduction